Inter-agency collaboration to support the COVID-19 response and maintain malaria services in Guinea and Sierra Leone: A social network analysis - Lukas Feddern; Ibrahima Kaba; Hanna-Tina Fischer; Brogan Geurts; Habibata Balde; Andrea Bernasconi; Vitali Merhi; Rike Böttcher; Karim Dumbuya; Francisco Pozo-Martin; Thurid Bahr; Sara Menelik-Obbarius; et al. (PLoS ONE, 2025)
Inter-agency networks are believed to be essential to maintaining essential health services during pandemics and to strengthening the resilience of health systems. Focusing on malaria during the COVID-19 pandemic as a case study, this paper investigates the network of organisations fighting malaria in Guinea and Sierra Leone, the changes in their interactions during the pandemic, and their collaboration with organisations addressing the COVID-19 response. We used a mixed-methods approach to analyse data from 36 semi-structured interviews with respondents involved in the COVID-19 response and malaria service provision in Guinea and Sierra Leone, as well as data from a social network survey conducted with a subsample of 21 out of the 36 respondents. Results from the thematic analysis of key informant interviews were used to contextualize the social network data, which was visualized as sociograms. We found that malaria stakeholders worked closely with key stakeholders involved in containing the COVID-19 pandemic. Their ability to support the COVID-19 response and contribute to maintaining essential malaria services was facilitated by the fact that established networks of malaria stakeholders had existed in both countries which comprised a variety of national and international organisations from the public, private and civil society sector working in different areas of malaria elimination. These stakeholders were able to maintain or even intensify their collaboration during the COVID-19 pandemic. The findings suggest that in resource-limited settings, the promotion of coordination mechanisms among stakeholders working on specific issues can strengthen linkages and consistency, thereby contributing to overall health system resilience and pandemic response.